(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Using method of synphytoindication, the values of certain climate and soil ecological factors of plant communities, located in the area of former shooting-range of the Azov sea coast, were calculated. The results of ordination analysis indicate that the majority of ecotopic characteristics of the studied area have intermediate position between diverse grass, fescue and feather grass steppes and fescue and feather grass steppes. However, it must be noted that the object system of Nature reserve fund of Ukraine, located in the steppe zone, is incomplete. That is why giving the protected status to the researched area will promote the development of Pryazov’ya ecological network.